2001
DOI: 10.1074/jbc.m008583200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Casein Kinase 2 α-Subunit Regulates Membrane Protein Traffic in the Human Hepatoma Cell Line HuH-7

Abstract: A previously isolated endocytic trafficking mutant (TRF1) isolated from HuH-7 cells is defective in the distribution of subpopulations of cell-surface receptors for asialoorosomucoid (asialoglycoprotein receptor (ASGR)), transferrin, and mannose-terminating glycoproteins. The pleiotropic phenotype of TRF1 also includes an increased sensitivity to Pseudomonas toxin and deficient assembly and function of gap junctions. HuH-7؋TRF1 hybrids exhibited a normal subcellular distribution of ASGR, consistent with the TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 39 publications
4
59
0
2
Order By: Relevance
“…The lack of this latter isoform resulted in a 60% reduction of total CK2 expression and hypophosphorylation of ASGP-Rs in the Trf1 mutant. Transfection of a cDNA encoding the CK2␣Љ isoform into the Trf1 mutant restored these cells to the parental phenotype, in which ASGP-Rs were phosphorylated normally and both the State 1 and State 2 endocytic pathways were active (52). Hence the expression of the CK2␣Љ isoform is required to maintain a functional State 2 endocytic pathway in HuH-7 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of this latter isoform resulted in a 60% reduction of total CK2 expression and hypophosphorylation of ASGP-Rs in the Trf1 mutant. Transfection of a cDNA encoding the CK2␣Љ isoform into the Trf1 mutant restored these cells to the parental phenotype, in which ASGP-Rs were phosphorylated normally and both the State 1 and State 2 endocytic pathways were active (52). Hence the expression of the CK2␣Љ isoform is required to maintain a functional State 2 endocytic pathway in HuH-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…An exciting discovery was recently made by Shi et al (52), who found that both Trf1 and HuH-7 cells expressed similar amounts of two CK2 catalytic subunit isoforms, CK2␣ and CK2␣Ј, but that the Trf1 mutant did not express a third and novel isoform, CK2␣Љ. The lack of this latter isoform resulted in a 60% reduction of total CK2 expression and hypophosphorylation of ASGP-Rs in the Trf1 mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Although more than 300 substrates of CK2 have been identified to date, little is known about the spatiotemporal substrate specificity of the different holoenzyme complexes, which contain various combinations of two individual catalytic subunits derived from the respective a, a 0 and a 00 isoforms, and a dimer of two non-catalytic, presumably regulatory b subunits [42,59,60]. It therefore appears that the myriad of regulatory effects caused by CK2 is reflected in a large and, with respect to its subunit composition, highly diverse population of holoenzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, Shi et al (2001) have reported a third catalytic subunit isoform, α''. Although both the isolated catalytic subunits and the holoenzyme are constitutively active, the ß subunits profoundly affect many properties of CK2, whose precise function is still poorly understood (Pinna, 2002).…”
Section: Resultsmentioning
confidence: 99%